2021
DOI: 10.1016/j.jbc.2021.100449
|View full text |Cite
|
Sign up to set email alerts
|

Selective targeting of the inactive state of hematopoietic cell kinase (Hck) with a stable curcumin derivative

Abstract: Hck, a Src family non-receptor tyrosine kinase (SFK), has recently been established as an attractive pharmacological target to improve pulmonary function in COVID-19 patients. Hck inhibitors are also well known for their regulatory role in various malignancies and autoimmune diseases. Curcumin has been previously identified as an excellent DYRK-2 inhibitor, but curcumin's fate is tainted by its instability in the cellular environment. Besides, small molecules targeting the inactive states of a kinase are desir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…HCK is the tyrosine protein kinase HCK, which plays an important role in hemopoiesis, regulation of the innate immune response and release of inflammatory molecules ( Podar et al, 2004 ). HCK has been identified as an important pharmacological target for improving lung function in patients with COVID-19 and has been significantly associated with COVID-19 in studies comparing healthy individuals with patients with severe COVID-19 ( Chen et al, 2022 , Chakraborty et al, 2021 ). In short, the selected hub targets elucidate the pharmacological mechanisms of action of cepharanthine for the treatment of COVID-19 at the level of antiviral, organismal metabolism, anticoagulation, and regulation of inflammatory and immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…HCK is the tyrosine protein kinase HCK, which plays an important role in hemopoiesis, regulation of the innate immune response and release of inflammatory molecules ( Podar et al, 2004 ). HCK has been identified as an important pharmacological target for improving lung function in patients with COVID-19 and has been significantly associated with COVID-19 in studies comparing healthy individuals with patients with severe COVID-19 ( Chen et al, 2022 , Chakraborty et al, 2021 ). In short, the selected hub targets elucidate the pharmacological mechanisms of action of cepharanthine for the treatment of COVID-19 at the level of antiviral, organismal metabolism, anticoagulation, and regulation of inflammatory and immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…The binding kinetics between tSH2 domain and ITAM-Y2P ligands were measured by following change in tryptophan fluorescence using a stopped-flow fluorimeter (SFM2000 BioLogic Spectrophotometer). The change in fluorescence intensity was measured at λ ex 290 nm, λ em 350 nm, and 10 °C ( 71 ). Hundred nanomolar of protein (tSH2 domain) in 20 mM Tris (pH 8.0), 150 mM NaCl, 5% glycerol, 5 mM β-mercaptoethanol, and 30 μM of ITAM-Y2P in same buffer, were mixed using syringe.…”
Section: Methodsmentioning
confidence: 99%
“…The identified PPI-hub genes also include three tyrosine-protein kinase family members: HCK, FGR, and LYN. These genes can deliver signals from cell surface receptors and play important roles in the regulation of innate and adaptive immune responses, integrin signaling, and responses to DNA damage and genotoxic agents (54)(55)(56)(57)(58). In myeloid and Blymphocyte lineage cells, HCK may help a couple of the Fc receptors to the activation of the respiratory burst (59), which may promote the formation of cytokine storms in COVID-19.…”
Section: A B D Cmentioning
confidence: 99%
“…MAPK3 encodes proteins that act in signaling cascade responses to regulate various cellular processes such as proliferation, differentiation and cell cycle progression in response to various extracellular signals (74,75). Previous studies on COVID-19 have suggested that FPR1 and MAPK3 may be potential therapeutic drug targets (54,76). In addition, our study also highlights the abnormal activation of platelets in severe COVID-19.…”
Section: A B D Cmentioning
confidence: 99%